The effect of organization restructuring on organization performance viewed from employee performance and leadership effectiveness at maluku provincial education office - Zainuddin Notanubun; Ribka Lemi Ririhena; John Rafafy Batlolona (Journal of Education and Learning (EduLearn), 2019)
The focus of this research is to comprehensively analyze the effect of organization restructuring on the performance of the organization, directly or indirectly, involving 276 employees in the education office and the Ministry of Education and Culture offices and collected by survey method. Data analysis was done using causal correlation technique to see the effect of organization restructuring on organization performance. The results of the research indicate that there is a direct influence of organization restructuring on organization performance. Another result is that there is an indirect effect of restructuring through employee performance and leadership effectiveness on organization performance. The influence of organization performance improvement is due to, organization restructuring implemented in Maluku Province education office has lead to behavior change, where the employees of education office were able to improve individual performance and can work together with the leadership as an efficient and effective structure. This has an impact on improving organization performance.